2011 IEEE International Conference on Communications (ICC) 2011
DOI: 10.1109/icc.2011.5962551
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for Joint Optimization of Monitor Location and Network Anomaly Detection

Abstract: Abstract-To reduce monitoring cost, the number of monitors to be deployed have to be minimized and the overhead of monitoring flows on the underlying network have to be reduced. In a recent work, we demonstrated, using ILP formulations, that there is a trade-off between theses two minimization objectives. However, we have shown that the trade-off could be efficiently balanced by jointly optimizing monitor location and anomaly detection costs. The problem is NP-complete, hence ILPs could not deliver solutions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…SiGe-pnp SAFE OPERATING AREA (SOA) In order to fully exploit the speed and performance advantages of SiGe-pnp's in product applications, such as the next generation automotive electronics, aerospace, military, and high-speed analog/RF products, an understanding of reliability is critical [97][98][99][100]. From a reliability perspective it is important to know where the boundaries of device performance versus device robustness can be pushed [101].…”
Section: Process In T Egrati Onmentioning
confidence: 99%
“…SiGe-pnp SAFE OPERATING AREA (SOA) In order to fully exploit the speed and performance advantages of SiGe-pnp's in product applications, such as the next generation automotive electronics, aerospace, military, and high-speed analog/RF products, an understanding of reliability is critical [97][98][99][100]. From a reliability perspective it is important to know where the boundaries of device performance versus device robustness can be pushed [101].…”
Section: Process In T Egrati Onmentioning
confidence: 99%
“…However the problem is NPComplete. Heuristics have been proposed for mono-domain networks in [2]. For multi-domain networks, the problem can be formulated as follows.…”
Section: B Problem Definitionmentioning
confidence: 99%
“…In our previous works, we have demonstrated that there is an interplay between these two minimization objectives. However, it turned out that the joint minimization of the two objectives balances efficiently this interplay [1], [2]. Therefore, our ILP formulation minimizes jointly the monitoring costs expressed above.…”
Section: Architecture and Cost Model Of Multi-domain Monitoringmentioning
confidence: 99%
See 2 more Smart Citations